Attitudes Toward Aging of Physical Therapists and Student Physical Therapists. (1st December 2014) - Blackwood, Jennifer; Sweet, Christina; Martin, Alison
ABSTRACT Aims: Attitudes toward aging have been reported to guide patterns of practice in healthcare; however, the current attitudes toward aging in physical therapy are unknown. Methods: Physical therapist (PT) and student physical therapist (SPT) members of the American Physical Therapy Association were invited to complete an anonymous online survey using a modified version of the 14-item University of California, Los Angeles-Geriatric Attitudinal Scale (UCLA-GAS) to examine attitudes toward aging. Differences between responses on each item of the UCLA-GAS were completed between groups and within three categories commonly reported in the UCLA-GAS. Results: Significant differences were found between the responses of PTs and SPTs on half of the items of the UCLA-GAS. Conclusions: PTs had slightly more positive attitudes toward aging, which may be a reflection of time spent with older adults and familiarity with the economics of geriatric physical therapy practice.